A comprehensive review on the applications of coal fly ash - Yao, Z.; Ji, X.; Sarker, Prabir; Tang, J.; Ge, L.; Xia, M.; Xi, Y. (Elsevier, 2015)
Coal fly ash, an industrial by-product, is derived from coal combustion in thermal power plants. It is one of the most complex anthropogenic materials, and its improper disposal has become an environmental concern and resulted in a waste of recoverable resources. There is a pressing and ongoing need to develop new recycling methods for coal fly ash. The present review first describes the generation, physicochemical properties and hazards of coal fly ash at the global level, and then focuses on its current and potential applications, including use in the soilamelioration, construction industry, ceramic industry, catalysis, depth separation, zeolite synthesis, etc. Finally, the advantages and disadvantages of these applications, themode of fly ash utilizationworldwide anddirections for future research are considered.